Empowering educational tourism managers by strengthening managerial capacity through field-based training in Pagelaran Village - Agung Winarno; Desti Nur Aini; Sopingi; Muhammad Nur Singgih; Naufal Dzakwana Muhammad (University of Merdeka Malang, 2025)
The Mentaraman Art and Cultural Educational Tourism Village faces challenges related to limited managerial capacity, low literacy in community-based tourism management, and suboptimal governance sustainability. This community service program aimed to strengthen the managerial capacity of tourism managers, particularly in planning, institutional organization, resource management, and tourism service standardization. An experiential learning–based capacity-building approach was applied through socialization, thematic training, field-based practice, technology application, evaluation, and continuous mentoring. The results indicate a significant improvement in managerial capacity across key indicators, including planning, coordination, institutional management, tourism guiding literacy, and digital technology utilization. Quantitative evaluation shows that over 80 percent of participants achieved good to very good competency levels and expressed positive perceptions of the effectiveness of field-based learning. The program also contributed to improving the quality and diversity of art and cultural tourism products, optimizing digital promotion, and strengthening community participation. Sustainability was supported through the formulation of a five-year tourism village development roadmap, initiation of village-level regulatory support, reinforcement of collaborative networks, and ongoing partnerships with higher education institutions. These findings demonstrate that experiential learning–based managerial capacity strengthening grounded in local potential is effective in promoting sustainable and professional management of art and cultural tourism villages.